2002
DOI: 10.1021/ja026512q
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric Resolution of 2-Aryl Propionic Esters with Hyperthermophilic and Mesophilic Esterases:  Contrasting Thermodynamic Mechanisms

Abstract: The enantiomeric resolution of 2-aryl propionic esters by hyperthermophilic and mesophilic esterases was found to be governed by contrasting thermodynamic mechanisms. Entropic contributions predominated for mesophilic esterases from Candida rugosa and Rhizomucor miehei, while enthalpic forces controlled this resolution by the esterase from the extremely thermoacidophilic archaeon, Sulfolobus solfataricus P1. This disparity in thermodynamic mechanism can be attributed to the differences in conformational flexib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The enzyme hydrolyzed the ( R )-ester of racemic ketoprofen methylester and showed an enantiomeric excess of 80% with a conversion rate of 20% in 32 h. In another study, the esterase Sso-Est1 from S. solfataricus P1 (Sehgal et al 2001 ) was identified as homolog to the mesophilic Bacillus subtilis ThaiI-8 esterase (CNP) (Quax and Broekhuizen 1994 ) and Candida rugosa lipase (CRL) (Lee et al 2001 ), which are used for the chiral separation of racemic mixtures of 2-arylpropionic methyl esters. The enzyme was characterized biochemically for its ability to resolve mixtures of ( R,S )-naproxen methyl ester under a variety of reaction environments (Sehgal and Kelly 2002 , 2003 ). Sso-Est1 showed a specific reaction toward the ( S )-naproxen ester in co-solvent reaction conditions with an enantiomeric excess of ≥90%.…”
Section: Properties Of Characterized Esterasesmentioning
confidence: 99%
“…The enzyme hydrolyzed the ( R )-ester of racemic ketoprofen methylester and showed an enantiomeric excess of 80% with a conversion rate of 20% in 32 h. In another study, the esterase Sso-Est1 from S. solfataricus P1 (Sehgal et al 2001 ) was identified as homolog to the mesophilic Bacillus subtilis ThaiI-8 esterase (CNP) (Quax and Broekhuizen 1994 ) and Candida rugosa lipase (CRL) (Lee et al 2001 ), which are used for the chiral separation of racemic mixtures of 2-arylpropionic methyl esters. The enzyme was characterized biochemically for its ability to resolve mixtures of ( R,S )-naproxen methyl ester under a variety of reaction environments (Sehgal and Kelly 2002 , 2003 ). Sso-Est1 showed a specific reaction toward the ( S )-naproxen ester in co-solvent reaction conditions with an enantiomeric excess of ≥90%.…”
Section: Properties Of Characterized Esterasesmentioning
confidence: 99%
“…On the other hand, the stereochemical purity of a chiral substance is often evaluated by the E value (11,12,14,15,17), meaning the enantiospecificity ratio. Defining E as the diastereospecificity ratio for the R,R and R,S diastereomers, it is expressed as Equation 5…”
Section: Resultsmentioning
confidence: 99%
“…The negative ∆∆S ‡ values indicate that the R,R isomer is more tightly bound to the enzyme in the transition state than is the R,S isomer. This is presumably due to favorable van der Waals interactions and hydrogen bonding between the R,R isomer and the amino acid side chains lining the binding sites in the complex (13,15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermophilic examples include enzymes described for Thermoanaerobacter spp. (Royter et al, 2009;Rao et al, 2011) and the archaeal genus Sulfolobus (Huddleston et al, 1995;Sehgal and Kelly, 2002;Ejima et al, 2004;Mandrich et al, 2007). Commercial use of psychrophilic lipases (Huston, 2008;Cavicchioli et al, 2010) has been moderate save for a few well-known examples such as the Candida antarctica lipases available from Sigma Aldrich and Novozymes.…”
Section: Transesterification Of Oilsmentioning
confidence: 99%